2004
DOI: 10.1590/s1415-47572004000200010
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic description of four species of Trigona (Jurine, 1807) (Hymenoptera, Apidae, Meliponini) from the State of Mato Grosso, Brazil

Abstract: The genus Trigona contains at least 31 species, but there have been few cytogenetic studies of this group. In this work, four species of Trigona (T. branneri, T. chanchamayoensis, T. hyalinata, and T. recursa) from the municipality of Cuiabá, in the State of Mato Grosso, Brazil, were studied. In all of the species, the females had 2n = 34 chromosomes and the males had n = 17. The C-banding patterns showed that the karyotypes of these species consisted mainly of acrocentric and pseudoacrocentric chromosomes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…However, most previous studies showed numeric variation as the main source of polymorphism (Brito et al, 1997;Araújo et al, 2002;Scher and Pompolo, 2003;Brown Jr. et al, 2004). The chromosome number 2n = 34 determined for Scaptotrigona xanthotricha agrees with previous studies on other Scaptotrigona species (Hoshiba and Imai, 1993;Rocha et al, 2003) and corroborates the numerical stability in the tribe Meliponini (Brito et al, 2003;Rocha et al, 2003;Costa et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, most previous studies showed numeric variation as the main source of polymorphism (Brito et al, 1997;Araújo et al, 2002;Scher and Pompolo, 2003;Brown Jr. et al, 2004). The chromosome number 2n = 34 determined for Scaptotrigona xanthotricha agrees with previous studies on other Scaptotrigona species (Hoshiba and Imai, 1993;Rocha et al, 2003) and corroborates the numerical stability in the tribe Meliponini (Brito et al, 2003;Rocha et al, 2003;Costa et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…The numeric stability observed in the karyotypes of the tribe Meliponini, with 2n = 34 as the predominant number, indicates that the differences observed are allied to structural chromosome changes, especially in the variable heterochomatin regions along the chromosome segments (Hoshiba and Imai, 1993;Rocha et al, 2003;Costa et al, 2004). Karyotype variation produced by structural chromosome rearrangements frequently occurs in heterochromatic regions (John, 1988;Sumner, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…T. spinipes Tarelho, 1973;Brito and Pompolo, 1997), T. cilipes , T. recursa (Tarelho, 1973;Costa et al, 2004), T. fuscipennis (Tarelho, 1973), T. branneri, T. hyalinata and T. chanchamayoensis (Costa et al, 2004). We also found another karyotypic difference, a large metacentric chromosome pair in the karyotype of T. fulviventris which was absent, or has not been reported, in the above cited species.…”
supporting
confidence: 50%
“…In contrast, DAPI + labeling was observed on chromosomes whose heterochromatin was weakly labeled by C banding, indicating a widespread distribution of the AT-rich heterochromatin. Costa et al (2004) found a predominance of GC-rich heterochromatin in T. branneri chromosomes but not in T. recursa. These authors did not perform DAPI staining on these two species.…”
mentioning
confidence: 82%
“…We wish to gain a better understanding of the nature of heterochromatin in the tribe Meliponini to verify if the Minimum Interaction Theory can be applied to stingless bees. Pertinent studies on Meliponini bees include those of Pompolo and Campos (1995) in Leurotrigona, Rocha et al (2003) in Friesomiellita and Tetragonisca angustula, Caixeiro (1999) in Plebeia, and Costa et al (2004) in Trigona. However, rather few species (about 80 out of 400 species) of stingless bees have been studied.…”
Section: General Features Of P Helleri and P Seridoensis Karyotypesmentioning
confidence: 99%